Base-load Cycling on a System with Significant Wind Penetration - Denny, Eleanor (My University, 2010)
Certain developments in the electricity sector may result in suboptimal operation of base-load generating units in countries worldwide. Despite the fact they were not designed to operate in a flexible manner, increasing penetration of variable power sources coupled with the deregulation of the electricity sector could lead to these base-load units being shut down or operated at partload levels more often. This cycling operation would have onerous effects on the components of these units and potentially lead to increased outages and significant costs. This paper shows the serious impact increasing levels of wind power will have on the operation of base-load units. Those base-load units which are not large contributors of primary reserve to the system and have relatively shorter start-up times were found to be the most impacted as wind penetration increases. A sensitivity analysis shows the presence of storage or interconnection on a power system actually exacerbates base-load cycling until very high levels of wind power are reached. Finally, it is shown that if the total cycling costs of the individual base-load units are taken into consideration in the scheduling model, subsequent cycling operation can be reduced.
PUBLISHED
Keywords: Energy; Electricity; Wind Energy; Generation; Power System Operation; Smart & Sustainable Planet